AL-QUR'AN AS A TRANSENDENT COMMUNICATION MEDIA - Rahmatika, Arina (QAULAN: Journal of Islamic Communication, 2021)
This research proves that human communication with God is a transcendent communication process that is important for human life and its success cannot be measured. Al Quran in this case as evidence of transcendent communication. The Qur'an is a medium of communication in the form of the word of God which was revealed to the Prophet Muhammad SAW for all humans through the angel Gabriel. While communication is the process of sending messages or information from the communicator to the communicant and then generating feedback. God in this context as a transcendent communicator, then his message is written in the Qur'an itself and humans as communicants and the Prophet is the one who delivers the news. Keywords: Al-Qur’an, media, Transcendent Communication